Pengembangan Sistem Informasi Pariwisata Geopark Ciletuh Menerapkan Metode User Centered Design - Firdaus, Hafidh; Hidayatullah, Deny (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
Ciletuh Geopark is a tourist attraction located in Sukabumi Regency, West Java, Indonesia. In addition, Ciletuh Geopark is one of the tours that has a lot of geology, biology, and culture. One of the places that has an attraction for local and foreign tourists is Palangpang Beach. Many people do not know information about Palangpang Beach. So the creation of a solution to make this system. This design is made with PHP with MySQL programming as the database. The method used in this system is User Centered Design. This application have some reason to made, that is help some people to get some information about Palangpang Beach.